2015
DOI: 10.18632/oncoscience.161
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of MET gene mutations

Abstract: C-MET proto-oncogene is a tyrosine kinase situated on chromosome 7. C-MET and its ligand hepatocyte growth factor/scatter factor (HGF/SF) play a role in proliferation, differentiation and organ development. C-MET genetic aberrations are found associated with driving tumorigenesis. In this retrospective study, we reviewed molecular analysis data gathered from a cancer institute during a two-year period (2010-2012). Upon detection of tumors harboring c-MET mutations, we determined the status of the other mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…N375S variant frequently occurs in Asians and its biological role is unclear. In preclinical studies of lung cancer, the loss of binding affinity of c‐MET to HGF by N375S variant was analyzed in silico and they showed N375S variant conferred resistance to SU11274, c‐MET inhibitor . However, our results suggested that SNU‐638 with the N375S variant was more sensitive to c‐MET inhibitors than the other cell lines which did not have that variant (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…N375S variant frequently occurs in Asians and its biological role is unclear. In preclinical studies of lung cancer, the loss of binding affinity of c‐MET to HGF by N375S variant was analyzed in silico and they showed N375S variant conferred resistance to SU11274, c‐MET inhibitor . However, our results suggested that SNU‐638 with the N375S variant was more sensitive to c‐MET inhibitors than the other cell lines which did not have that variant (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…34 High c-MET expression or highly activated c-MET has also been reported in many types of tumors including CRC as c-MET is a proto-oncogene that is crucial for cancer progression. 35 To investigate any mechanistic or functional link between BRCA2 mutations and c-MET overexpression we used siRNA knockdown to effectively abrogate BRCA2. We hypothesized that BRCA2 deficiency would lead to increased double-strand DNA breaks in dividing cells or DNA damage exposed cells.…”
Section: Discussionmentioning
confidence: 99%
“…MET alterations (mainly involving overexpression) have been described in numerous human tumors, and they are often associated with a poor outcome (Scagliotti G, Novello, & von Pawel, ). Activating point mutations have been reported in sporadic and inherited forms of renal carcinoma, hepatocellular carcinoma, and several other cancer types (Ma et al., ; Schmidt et al., ; Zenali et al., ). A remarkably high incidence of somatic MET mutations was found in a series of 23 metastatic lesions arising from unknown primaries (Stella et al., ).…”
mentioning
confidence: 99%